The immune network in thyroid cancer - Galdiero, Maria Rosaria (Oncoimmunology, 2016)
The immune system plays critical roles in tumor prevention, but also in its initiation and progression. Tumors are subjected to immunosurveillance, but cancer cells generate an immunosuppressive microenvironment that favors their escape from immune-mediated elimination. During chronic inflammation, immune cells can contribute to the formation and progression of tumors by producing mitogenic, prosurvival, proangiogenic and lymphangiogenic factors. Thyroid cancer is the most frequent type of endocrine neoplasia and is the most rapidly increasing cancer in the US. In this review, we discuss recent findings on how different immune cells and mediators can contribute to thyroid cancer development and progression.